NEW REMAINS OF MICROSTONYX (S UIDAE, ARTIODACTYLS) F ROM THE MIOCENE OF PAKISTAN - Z. Ahmad; K. Aftab; S. Azad; M. A. Khan (Journal of Animal and Plant Sciences, 2019)
The remains of Microstonyx are discovered during the fossil excavation from the Potwar plateau, northern Pakistan. The detailed comparison with the Dicoryphochoerus titanoides and Hippopotamodon sivalense, the specimens are assigned to Microstonyx major. The genus Microstonyx is characterized by elongated I2 and I3, gigantic suids but smaller than Hippopotamodon. The new molars of the rare species M. major reported here are recovered from Ava and Kund localities of the Siwalik Group.
Keywords: Suidae; Chinji; Siwaliks; Paleontology; Taxonomy